2016
DOI: 10.1016/j.pnpbp.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number is reduced in male combat veterans with PTSD

Abstract: This study provides the first evidence of: (i) a significant decrease of mtDNAcn in combat PTSD, (ii) a possible "inverted-U" shaped relationship between PTSD symptom severity and mtDNAcn within PTSD subjects, and (iii) a direct correlation of mtDNAcn with positive affectivity within PTSD subjects. Altered mtDNAcn in PTSD may reflect impaired energy metabolism, which might represent a novel aspect of its pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 79 publications
(90 reference statements)
4
50
0
Order By: Relevance
“…Multiple physiological systems at the neuronal, metabolic, inflammatory, genomic and epigenomic levels are known to be affected in PTSD 2 , 3 . Previous studies from our PTSD Systems Biology consortium reported associations between PTSD and insulin resistance 4 , inflammation 5 , reduced mitochondrial copy number 6 , and lower methylation of the glucocorticoid receptor (NR3C1) gene 7 in the same cohorts assessed in the present study. The data from animal models and humans with PTSD reveal association between inflammation and metabolic syndrome 8 .…”
supporting
confidence: 65%
“…Multiple physiological systems at the neuronal, metabolic, inflammatory, genomic and epigenomic levels are known to be affected in PTSD 2 , 3 . Previous studies from our PTSD Systems Biology consortium reported associations between PTSD and insulin resistance 4 , inflammation 5 , reduced mitochondrial copy number 6 , and lower methylation of the glucocorticoid receptor (NR3C1) gene 7 in the same cohorts assessed in the present study. The data from animal models and humans with PTSD reveal association between inflammation and metabolic syndrome 8 .…”
supporting
confidence: 65%
“…A few psychiatric studies have examined intracellular mtDNA-cn (primarily in leukocytes) with conflicting results. Reduced mtDNAcn has been reported in post-traumatic stress disorder 47 and in relation to depressive symptoms among elderly communitydwelling women without MDD. 48,49 Higher leukocyte mtDNA-cn has been reported in autism 50 and lifetime psychopathology in healthy people.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrial content in granulocytes from male combat veterans with post‐traumatic stress disorder (PTSD) has also been found to be decreased (Bersani et al . ). While cortisol was not measured in the PTSD study, cortisol levels are known to be dysregulated in individuals with PTSD (Wichmann et al .…”
Section: Discussionmentioning
confidence: 97%
“…Maternal glucocorticoids have been shown to reduce mitochondrial content in fetal heart tissues (Richards et al 2014), and in vitro studies have demonstrated decreased mitochondrial content in endothelial cells exposed to glucocorticoids (Gero & Szabo, 2016). Mitochondrial content in granulocytes from male combat veterans with post-traumatic stress disorder (PTSD) has also been found to be decreased (Bersani et al 2016). While cortisol was not measured in the PTSD study, cortisol levels are known to be dysregulated in individuals with PTSD (Wichmann et al 2017), and may have contributed to the decreased mitochondrial content in the study.…”
Section: Effects Of Corticosterone On Mitochondrial Functionmentioning
confidence: 99%